Colorimetric detection of Cu2+ based on the formation of peptide–copper complexes on silver nanoparticle surfaces - Ghodake, Gajanan Sampatrao; Shinde, Surendra Krishna; Saratale, Rijuta Ganesh; Kadam, Avinash Ashok; Saratale, Ganesh Dattatraya; Syed, Asad; Ameen, Fuad; Kim, Dae-Young (Beilstein Journal of Nanotechnology, 2018)
We developed a colorimetric method for the rapid detection of copper ions (Cu2+) in aqueous solution. The detection of Cu2+ is based on coordination reactions of Cu2+ with casein peptide-functionalized silver nanoparticles (AgNPs), leading to a distinct color change of the solution from yellow to red. The developed method has a good detection limit of about 0.16 µM Cu2+ using 0.05 mL of AgNPs stock solution and a linearity in the range of 0.08–1.44 µM Cu2+ with a correlation coefficient of R2 = 0.973. The developed method is a useful tool for the detection of Cu2+ ions. Furthermore, it can be used for monitoring Cu2+ in water at concentrations below the safe limit for drinking water set by the World Health Organization.
Keywords: absorbance; dispersion; drinking water; rapid detection; UV spectroscopy